Theft of Controlled Substances in Long-Term Care Homes: An Exploratory Study. (July 2023) - Caspi, Eilon; Xue, Wei-Lin; Liu, Pi-Ju
The theft of controlled substances has been studied in the community and healthcare settings including hospitals, pharmacies, hospice, and pain clinics. However, research on these thefts in long-term care homes has yet to be published. This exploratory study makes first steps toward bridging this gap. Using 107 Minnesota Department of Health's investigation reports substantiated as "drug diversion" between 2013 and 2021 in assisted living residences and nursing homes, we found that 11, 328.5 tablets were stolen from 368 residents (97.5% were controlled substances), with over 30 tablets stolen per resident. We also identified the types of medications stolen, duration of theft, extent to which nurses stole the medications or were those initially suspecting thefts, and the role of surveillance cameras in confirming allegations. The findings could raise awareness to this form of elder mistreatment in long-term care homes and call for action to address it.